2015
DOI: 10.5527/wjn.v4.i2.185
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of glomerular haematuria

Abstract: Haematuria was known as a benign hallmark of some glomerular diseases, but over the last decade, new evidences pointed its negative implications on kidney disease progression. Cytotoxic effects of oxidative stress induced by hemoglobin, heme, or iron released from red blood cells may account for the tubular injury observed in human biopsy specimens. However, the precise mechanisms responsible for haematuria remain unclear. The presence of red blood cells (RBCs) with irregular contours and shape in the urine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 86 publications
1
29
0
2
Order By: Relevance
“…We found that it was greater than in MCD, and similar in its extent to the area measured in acute transplant glomerulitis [16]. Endothelial cell enlargement may indicate cell damage and contribute to the development of haematuria, with negative prognostic implications [4,12]. The number of macrophages in glomeruli was positively correlated with diffuse deposition of IgA and fibrinogen, a result, to the best of our knowledge, shown for the first time.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We found that it was greater than in MCD, and similar in its extent to the area measured in acute transplant glomerulitis [16]. Endothelial cell enlargement may indicate cell damage and contribute to the development of haematuria, with negative prognostic implications [4,12]. The number of macrophages in glomeruli was positively correlated with diffuse deposition of IgA and fibrinogen, a result, to the best of our knowledge, shown for the first time.…”
Section: Discussionsupporting
confidence: 62%
“…In IgAN the mechanism of haematuria is unknown, endothelial cell damage and alterations of the glomerular basal membrane may contribute to its development [4,12]. Whether endothelial cell enlargement is present in IgAN glomeruli has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…ROS destroy lipid membranes, proteins and nucleic acids [50] and induce apoptosis of epithelial tubular cells [51]. Furthermore, iron causes inflammation and damage to the kidney which is manifested as fibrosis [52].…”
Section: Heme Cytotoxicitymentioning
confidence: 99%
“…According to Liu et al (2014) the mesangial cell regulated fibronectin production by caveolin-1 phosphorylation. Kidney disease such as fibronectin glomerulopathy and fibrillary glomerulonephritis followed by alteration in glomerular basement membrane structure and other extracellular components leading to weaker and easily extracellular ruptured structures (Yuste et al, 2015). Therefore, fibronectine deregulation in the interstitial space causes imbalance between soluble and insoluble fibronectin leading to fibronectin glomerulopathy, although the prevalence rate is higher in adolescence (Deltas et al, 2012).…”
Section: Discussionmentioning
confidence: 93%